2009
DOI: 10.1179/174313209x444062
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcome of carotid artery stenting or antiplatelet therapy in patients with severe carotid artery stenosis

Abstract: Carotid artery stenting combined with antiplatelet therapy may be helpful for high-risk patients with severe carotid artery stenosis. The benefit/harm of intra-artery intervention for patients with stroke or TIA suffered as a result of severe carotid artery stenosis in the long-term needs further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In comparison with CEA, CAS is focused for its benefits in the treatment of carotid artery stenosis. [1][2][3] Previous researches suggested that CAS is equally effective and safe in the treatment of carotid artery disease. [4][5][6] Recently, with the accumulation of physician's experience, the improvement in equipment and material, and especially the routine use of cerebral embolic protection devices, CAS surgery now have even better performance than that reported for CEA surgery in many centers.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with CEA, CAS is focused for its benefits in the treatment of carotid artery stenosis. [1][2][3] Previous researches suggested that CAS is equally effective and safe in the treatment of carotid artery disease. [4][5][6] Recently, with the accumulation of physician's experience, the improvement in equipment and material, and especially the routine use of cerebral embolic protection devices, CAS surgery now have even better performance than that reported for CEA surgery in many centers.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported that perhaps aspirin use provides a protective effect against ISR. [33][34][35] The most important lesson from this finding for our group is that we should strive to achieve >95% compliance with aspirin therapy in all our carotid patients. Unexpectedly, under univariate analysis, we found that statin use preoperatively or at discharge was associated with an increased risk for ISR.…”
Section: Discussionmentioning
confidence: 99%